The biochemical and molecular basis of Hypoxanthine-guanine phosphoribosyltransferase deficiency - Marinaki, Anthony Marin (Division of Chemical Pathology, 2018)
Hypoxanthine-guanine phosphoribosyltransferase (HPRT) catalyses the first step in purine salvage. A complete deficiency of the enzyme results in the devastating neurological symptoms of the Lesch-Nyhan syndrome. The Lesch-Nyhan syndrome is characterised by purine overproduction leading to, hyperuricemia and gout and a central nervous system disorder characterised by severe, spasticity, choreoathetosis, mental retardation and compulsive self-mutilatory behaviour, A partial deficiency of the enzyme results in purine overproduction, gout and occasionally, mild neurological symptoms. Patients are spared the compulsive self-mutilation of the Lesch-Nyhan syndrome. The major part of the thesis consists of the characterisation of the molecular defects in nine patients with the Lesch-Nyhan syndrome. The polymerase chain reaction was used to amplify reverse transcribed HPRT mRNA. The coding region of the amplified HPRT cDNA was either directly sequenced, or cloned and sequenced. All the mutations characterised were insertion or deletion events which resulted in premature termination of the predicted protein. Three patients were found to have a deletion of exon 7, two patients had single base insertions, while two patients appeared to have a complete deletion of the HPRT gene. An insertion in one patient was the result of a mutation within. intron 6 which created a new splice donor site. The new splice donor site in concert with a cryptic splice acceptor resulted in the creation of a new exon. A deletion of exons 2, 3 and 4 in another patient was found to lead to the alternative splicing of exon 5. These unusual splice junction mutations provided in viva support for the exon definition model of pre-mRNA splicing.